CHITOSAN AS ANTIFUNGAL IN CHANNA STRIATA COLLAGENCHITOSAN FOR WOUND HEALING - Andini, Ary; Prayekti, Endah (Jurnal Ilmu Kesehatan dan Kesehatan, 2019)
The Snakehead fish contains high protein that was mostly used as a treatment during healing process in either invasive or passive surgery. Therefore, it could be developed as well as a mixture of wounds dressing for skin healing. The aim of this study was to know the effect of  combination of concentrations between chitosan and collagen of  Snakehead fish  (Channa striata) skin and scales on fungal total number recovered from the composite. Snakehead fish skin and scales was treated by soaking in 2% HCl solvent for 48 hours to obtain collagen from its filtrate. Filtrate obtained continued to neutralize with 1 M NaOH until soluble collagen  appeared. Collagen obtained in this study then  mixed with 2% chitosan liquid to make wound dressing in various concentrations group. Combination of colagen mixture in this study were chitosan liquid only as control, 25% collagen-75% chitosan (C1), 50% collagen-50% chitosan (C2) and 75% collagen-25% chitosan (C3). The study results showed that on Control, C1 and C2 group there was no fungal contamination, but on C3 group there was contamination of fungal with total counting about 2,43 x 103 CFU. Based on statistically test showed that there was discrepancy for each group with p-value was 0,02 (p<0,05).